2009
DOI: 10.1093/rheumatology/kep141
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life, employment and disability in patients with Sjögren's syndrome

Abstract: SS has a large impact on HR-QOL, employment and disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
143
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(158 citation statements)
references
References 21 publications
7
143
0
8
Order By: Relevance
“…In broad terms the findings of increased work disability in pSS are in keeping with the small number of previous studies 3,4,5 . One clear and consistent message from all of these studies, conducted on different populations, with different experimental designs and different comparators, showed that work disability, including sick leave and disability pension, is significantly higher among patients with pSS than in the general population.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…In broad terms the findings of increased work disability in pSS are in keeping with the small number of previous studies 3,4,5 . One clear and consistent message from all of these studies, conducted on different populations, with different experimental designs and different comparators, showed that work disability, including sick leave and disability pension, is significantly higher among patients with pSS than in the general population.…”
supporting
confidence: 89%
“…One clear and consistent message from all of these studies, conducted on different populations, with different experimental designs and different comparators, showed that work disability, including sick leave and disability pension, is significantly higher among patients with pSS than in the general population. Mandl, et al also demonstrate that work disability in pSS is not associated with systemic disease activity (measured with the ESSDAI), and this is also consistent with previously published studies 3,4,5 .…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Due to the range of medical complications associated with SS, it is not surprising that the disease is associated with significant impairments in quality of life [23][24][25][26][27] and functioning [25,28]. Patients with SS also have a high rate of depression [26].…”
Section: Clinical Manifestations Of Ssmentioning
confidence: 99%
“…[1] pSS is a disabling disease and has a large effect on health-related quality of life. [2] Besides symptomatic treatments that improve dryness, no effective treatments have yet been approved for use in pSS. However, treatment with biologic disease-modifying antirheumatic drugs (DMARDs) has shown promising outcomes.…”
Section: Introductionmentioning
confidence: 99%